2022
DOI: 10.1039/d2cp04032h
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and challenges of carbon materials in the practical applications of lithium metal anode: a review

Abstract: Lithium (Li) metal is strongly considered to be the ultimate anode for the next generation of high-energy-density rechargeable batteries due to its lowest electrochemical potential and highest specific capacity. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…12–15 Organic anode materials have widely attracted the attention of researchers because of their designable molecular structure, abundant raw materials, environmental friendliness and high capacity. 16–21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12–15 Organic anode materials have widely attracted the attention of researchers because of their designable molecular structure, abundant raw materials, environmental friendliness and high capacity. 16–21…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Organic anode materials have widely attracted the attention of researchers because of their designable molecular structure, abundant raw materials, environmental friendliness and high capacity. [16][17][18][19][20][21] However, organic electrodes have three shortcomings that cannot be ignored despite their high capacity: easy to dissolve in electrolytes, low electrical conductivity and low utilization rate of active sites. The main solutions available for this are leveraging polymer chains as a highly stable framework, introducing multiple active groups, and compounding organic macromolecules with carbon materials, such as graphene or carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…With the current demand for high energy density, lithium (Li) metal has been considered as the most promising next-generation anode due to its extremely high theoretical capacity (3860 mAh cm –3 ) and low redox potential (−3.04 V vs standard hydrogen electrode). However, the disorderly growth and volume expansion of lithium metal can result in fragile solid electrolyte interface (SEI) rupturing and consumption of electrolyte, seriously impeding its practical application. Additionally, the growth of lithium dendrites due to uneven nucleation also poses some safety hazards. The utilization of 3D hosts is regarded as a prospective strategy for its efficient reduction of local current density and volume expansion. Among these hosts, carbon nanofiber cloth has been attracting attention because of its higher conductivity, low density, and designability. Unfortunately, the nonuniformity of lithium nucleation and the tendency to deposit on top allow a large amount of lithium storage space within the 3D hosts to be wasted, which limits its advantages.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 Carbon materials and their composites with high electric conductivity and economic benefits are promising candidates in anode-free LMBs thanks to their comparable advantages, such as decreasing the nucleation energy barrier and suppressing dendrite formation. 13 Therefore, many innovatively designed carbon materials have been proposed to address the issues of LMAs. 14 Zhang and co-authors 15 recently found that the formation of "dead Li" on the surface of the graphite anode that prevents electron access can increase the average delithiation potential, while the graphite intercalation compounds inside the graphite can still be delithiated normally.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these strategies, the advantages of hosts are obvious because of significantly reducing the local current density, availably improving the stability of metallic Li deposition, and directly suppressing dendritic Li formation. Carbon materials and their composites with high electric conductivity and economic benefits are promising candidates in anode-free LMBs thanks to their comparable advantages, such as decreasing the nucleation energy barrier and suppressing dendrite formation . Therefore, many innovatively designed carbon materials have been proposed to address the issues of LMAs .…”
Section: Introductionmentioning
confidence: 99%